Biophotonics in Healthcare: Advancements in Light-Based Imaging and Therapy - mala tohy, Meena Jamal Khader fatiha; Yahya, Fatima Nazar ahmad; Alneemy, Haneen Fouad Ali Ahmad; Ebrahem, Duaa Sadam; Yahya, Manar Mahmoud (American Journal of Botany and Bioengineering, 2025)
Biophotonics—a rapidly expanding field of light-based technology—provides powerful advances in light-based science, medicine, biology, environmental monitoring, national defense, and automation. It includes—as a broad definition—the interactions and applications of macro, micro, and nano-scale photons with biosystems and, importantly, incorporates advanced biophotonics methods to address critical light-tissue interaction issues for the advancement of physical, chemical, and biological measurements in prevention, diagnosis, and treatment of health disorders For example, biophotonic-based laboratory tests can detect diseases at earlier stages, thereby permitting easier and more effective healing. To fulfill Van Leeuwenhoek’s pioneering idea of investigating processes in-vivo, modern biophotonics has benefited from advanced light sources, detectors, and new approaches of interaction of light with biological tissues. Innovations in biophotonics have already provided (1) numerous transformative light-based imaging and therapy tools currently affecting the way healthcare is delivered; (2) many powerful lab-on-a-chip platforms for point-of-care detection of biomarkers to monitor diseases and customize drug delivery; and (3) new lighting technology tools to study the effects of light on circadian rhythm and overall health. The light-based injection and treatment of malignant tissues based on immunotherapy opens a new paradigm in oncology with the powerful side effect without affecting normal tissues.